DESKRIPSI PERBEDAAN PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS ANTARA PENGGUNAAN MODEL PROBLEM BASED LEARNING DAN GUIDED DISCOVERY LEARNING DENGAN E-LEARNING - Livia Eunike Paut; Sulistiawati Sulistiawati; Klara Iswara Sukmawati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Mathematical communication ability is a mathematical ability have to own by students. Although, mathematical communication skills of student is still low. The ways to increase mathematical communication ability of students is applying problem based learning model (PBL) and guided discovery learning model (GDL). This research aimed to describe the differences of mathematical communication ability’ enhancement between PBL and GDL by E-learning. The research’s method is descriptive quantitative. The subject is student of mathematics education program and physics education program at STKIP Surya in academic year 2018/2019 from Ambon, that was separated into PBL class and GDL class, each of class contained 5 students heterogeneously. The instrument using in this research was test and observation sheet. The data analyzed using statistic descriptive and gain (the enhancement between pretest and posttest). The result of this research is the enhancement of mathematical communication skills of two classes is different, 15 for PBL and 14 for GDL.